Pharmacist management of atrial fibrillation in UK primary care: a qualitative study - Shahd Al-Arkee; Julie Mason; Antje Lindenmeyer; Zahraa Jalal (Taylor & Francis Group, 2022)
Background Atrial fibrillation (AF) affects up to 2% of the UK population. AF is a potentially long-term condition that needs management, and as such primary care pharmacists may have a substantial role in supporting the management of AF. Objectives This study aims to explore the role of primary care pharmacists, working in community pharmacies and general practices (GPs), in supporting the management of AF. Furthermore, this study investigates pharmacists' confidence in their knowledge and their attitudes towards incorporating AF-associated mobile apps use into their current practice. Methods A qualitative study was conducted, using one-to-one semi-structured, audio-recorded interviews with primary care pharmacists. The topic guide was developed based on pharmacy visits and included the most relevant constructs from the 'consolidated framework for implementation research (CFIR)'. All interviews were audio-recorded, transcribed verbatim and thematically analysed until saturation was achieved, guided by Braun and Clarke's 6-step research method. This study was given a favourable opinion on 5 September 2019 by the University of Birmingham (UOB) Research Ethics Committee (Reference ERN_19-0908). Results Thematic saturation was achieved after 11 interviews with primary care pharmacists (seven community pharmacists, and four GP pharmacists). Three main themes emerged relating to (1) the clinical role of pharmacists in the management of AF; (2) knowledge and awareness; and (3) prioritisation of resources. The first highlighted that primary care pharmacists were an underutilised resource within AF management. The second demonstrated that pharmacists, especially those based in the community, felt a lack of confidence in their knowledge of AF and its management, mainly community pharmacists due to other roles taking precedence over clinical roles. Both community and GP pharmacists expressed the need to have further training in this therapeutic area to be able to effectively support patients with AF. The third shed light on the pharmacists' views relating to the technological revolution in healthcare. Pharmacists expressed an interest in using apps to support their current practice. Conclusions Primary care pharmacists supported an extended care to AF management from screening to consultations, yet the provision of such services remains limited and inconsistent. Future research should focus on understanding the ways in which pharmacists' role can be adapted toward greater involvement in clinical care.